The role of youth in the promotion of peace through community policing - Othman, Jamilah; Yero, Aliyu (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
The role of youth for the promotion of peaceful coexistence and crime controls cannot be deemphasized in all human societies; youth represent a building block for the future of human race and thus must be actively engaged in all efforts towards peace making peace promotion and peace development as sidelining them could likely spell doom for the immediate and future harmony. As a strategy for crime control and peace development, community policing most carry along all segments of people to succeed most especially the youth. Using existing literature, this paper posits that aggressive engagement of the youth through community policing will go a long way in guaranteeing the survival on a long term bases of community policing as a strategy as well as overall societal peace development, it is only when there is peace that the society can develop. Recognizing that this central role of attaining peace through youth engagement in community policing is inevitable, the paper conclude that failure to do this have the potential of undermining developmental efforts and poses a threat to the survival of community policing. In effect therefore, the paper is pushing for a “Youth-Focused” community policing.